2019
DOI: 10.22456/1679-9216.90279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treatment with Quercetin on the Quality of Cryopreserved Bovine Semen

Abstract: Background: Semen cryopreservation is one of the most common biotechnologies in the reproduction of animals of agricultural interest, especially bulls. However, cryopreservation can be harmful to sperm cells, with susceptibility to oxidative stress being one of the causes. The addition of antioxidants such as quercetin may inhibit and/or reduce such damage, reducing fertility. Quercetin can increasing sperm motility and interaction capacity between spermatozoa-oocyte, to increase cellular metabolism and reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…In an experiment with Brahman bulls, Tironi et al (2019) tested lower concentrations (5, 15, and 20 μg mL -1 ), and although they observed an increase in TM and PM values ​​in semen supplemented with quercetin, they also found no significance in their results for the doses tested. However, the same authors found that the LIN values ​​increased as the dose of the antioxidant increased, being higher ( P < 0.05 ) than the control at the highest concentration of quercetin.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In an experiment with Brahman bulls, Tironi et al (2019) tested lower concentrations (5, 15, and 20 μg mL -1 ), and although they observed an increase in TM and PM values ​​in semen supplemented with quercetin, they also found no significance in their results for the doses tested. However, the same authors found that the LIN values ​​increased as the dose of the antioxidant increased, being higher ( P < 0.05 ) than the control at the highest concentration of quercetin.…”
Section: Discussionmentioning
confidence: 87%
“…Its activity has already been described for several other functions, such as anti-tumor, anti-inflammatory, and antimicrobial, in addition to its antioxidant activity ( Santos and Rodrigues, 2017 ). Moreover, quercetin's ability to maintain sperm viability has been successfully adopted in several species such as horses ( Gibb et al, 2013 ; McNiven and Richardson, 2006 ), goats ( Silva et al, 2016 ), cattle ( Tironi et al, 2019 ), buffalo ( Ahmed et al, 2019 ), wild pigs ( Winn and Whitaker, 2018 ), and humans ( Zribi et al, 2012 ), demonstrating promising results.…”
Section: Introductionmentioning
confidence: 99%
“…Outro estudo executado por Tironi et al (2019), concluiu que a adição da quercetina no diluente seminal, levou ao aumento na velocidade do espermatozoide e, quando comparado ao grupo controle, os espermatozoides mantiveram taxa metabólica mais alta, após o processo de descongelação.…”
Section: Estudos Sobre Os Efeitos Da Quercetinaunclassified